Pro DNS and BIND 10 - Aitchison, Ron.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2011)
Pro DNS and BIND 10 guides you through the challenging array of features surrounding DNS with a special focus on the latest release of BIND, the world$1 (Bs most popular DNS implementation. This book unravels the mysteries of DNS, offering insight into origins, evolution, and key concepts like domain names and zone files. This book focuses on running DNS systems based on BIND 10, the first stable release that includes support for the latest DNSSEC standards. Whether you administer a DNS system, are thinking about running one, or you simply want to understand the DNS system, then this book for you. Pro DNS and BIND 10 starts with simple concepts, then moves on to full security-aware DNSSEC configurations. Various features, parameters, and Resource Records are described and illustrated with examples. The book contains a complete reference to zone files, resource records, and BIND's configuration file parameters. You can treat the book as a simple paint-by-numbers guide to everything from a simple caching DNS to the most complex secure DNS (DNSSEC) implementation. Background information is included for when you need to know what to do and why you have to do it, and so that you can modify processes to meet your unique needs.s
Keywords: Computer science; Computer Science; Computer Science, general